One-pot synthesis of 5-hydroxymethylfurfural by cellulose hydrolysis over highly active bimodal micro/mesoporous H-ZSM-5 catalyst - Nandiwale, Kakasaheb Y.; Galande, Nitish D.; Thakur, Pratika; Sawant, Sanjay D.; Zambre, Vishal P.; Bokade, Vijay V. (ACS Sustainable Chemistry & Engineering, 2014)
Direct synthesis of 5-hydroxymethylfurfural (5-HMF), a useful renewable biofuel and biochemical, was systematically studied by hydrolysis of microcrystalline cellulose over Bimodal-HZ-5 zeolite. Bimodal-HZ-5 zeolite obtained by post-synthesis modification of H-ZSM-5 with desilication was found to be a potential heterogeneous catalyst with 67% cellulose conversion and 46% yield of 5-HMF. Bimodal-HZ-5 was observed to be reusable for four cycles, without any loss in activity. The detailed optimization of process parameters and catalyst reusability are also presented. The present study opens a new avenue for the renewable one-pot synthesis of 5-HMF, a valuable product.
Keywords: 5-Hydroxymethylfurfural; Biomodal-HZ-5; glucose; Hydrolysis; Microcrystalline cellulose

One step synthesis of ethyl levulinate biofuel by ethanolysis of renewable furfuryl alcohol over hierarchical zeolite catalyst - Nandiwale, Kakasaheb Y.; Pande, Ashwini M.; Bokade, Vijay V. (RSC Advances, 2015)
Ethanolysis of renewable furfuryl alcohol (FAL) to ethyl levulinate (EL) biofuel over various zeolites viz. H-ZSM-5 (microporous, medium pore), Hierarchical-HZ-5 (combination of micro-and meso pore), H-Beta (microporous, large pore) and Ultra Stable Y (USY, microporous, large pore) was studied in detail. To the best of our knowledge, probably for the first time, Hierarchical-HZ-5 synthesized by desilication post-treatment has been employed as a heterogeneous catalyst for ethanolysis of FAL. The synthesized catalysts were characterized by powder X-ray diffraction (PXRD), temperature programmed NH3 desorption (TPAD), Energy dispersive X-ray analysis (EDAX), etc. Response surface methodology (RSM) with Box-Behnken experimental design (BBD) was used to investigate the influence of three crucial process variables of ethanolysis such as ethanol to FAL molar ratio, percent catalyst loading and reaction temperature on EL yield. The optimization tool of design expert software was employed to obtain the optimum reaction parameters for FAL ethanolysis over Hierarchical-HZ-5 catalyst. Three intermediates of FAL ethanolysis reaction such as, ethoxymethylfuran (EMF), 4,5,5-triethoxypentan-2-one and diethyl ether (DEE) have been identified and quantified from the product mixture with the aid of Gas Chromatography-Mass Spectroscopy (GC-MS). Hierarchical-HZ-5 was found to be a potential catalyst for ethanolysis of FAL with 73% EL yield and 26% EMF yield at optimized process parameters.

Optimization by box-behnken experimental design fur synthesis of n-hexyl levulinate biolubricant over hierarchical H-ZSM-5: an effort towards agricultural waste minimization - Nandiwale, Kakasaheb Y.; Bokade, Vijay V. (Process Safety and Environmental Protection, 2016)
The present study is devoted to develop efficient catalytic process for conversion of agricultural waste feedstock to value added chemicals. In this context, the n-hexyl levulinate, a renewable biolubricant was synthesized by esterification of biomass derived levulinic acid (LA) with n-hexanol in a closed batch system. Hierarchical-HZ-5 (modified H-ZSM-5) was used as a heterogeneous acid catalyst. There are no reports available on the synthesis of n-hexyl levulinate biolubricant using renewable levulinic acid. The process variables such as catalyst to LA ratio (X-1), n-hexanol to LA molar ratio (X-2), reaction time (X-3) and reaction temperature (X-4) were optimized by response surface methodology (RSM), using the Box-Behnken model. Analysis of variance was done to check the suitability and significance of the quadratic model. The yield of n-hexyl levulinate obtained was 97% with 100% selectivity at optimum process parameters. The RSM analysis predicted that catalyst to LA ratio is most significant (value of p < 0.0001) and n-hexanol to LA molar ratio is least significant (value of p = 0.0064) process parameter in esterification. The quadratic model established was revealed to be suitable and statistically precise with correlation value (R-2) of 0.9837 to predict the yield of n-hexyl levulinate. (C) 2015 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Agricultural waste feedstock; Esterification; Hierarchical-HZ-5; n-Hexyl levulinate; Optimization; Response surface methodology

One-pot cascade conversion of renewable furfural to levulinic acid over a bifunctional H3PW12O40SiO2 catalyst in the absence of external H-2 - Nandiwale, Kakasaheb Y.; Vishwakarma, Mona; Rathod, Simmy; Simakova, Irina; Bokade, Vijay V. (Energy & Fuels, 2021)
The conversion of biomass-derived furfural (FUR) to levulinic acid (LA), a versatile platform chemical, involves catalytic hydrogenation of FUR followed by acid hydrolysis to LA. However, this two-step process demands expensive separation and purification of the furfuryl alcohol (FAL) intermediate. Herein, we demonstrate an ingenious catalytic strategy for the one-pot cascade conversion of FUR to LA over a bifunctional catalyst without using pure external H-2. Isopropyl alcohol (IPA) served a dual role as a hydrogen donor and solvent while inhibiting the side reactions. Catalysts with a tunable surface area and acidity were synthesized by impregnating different percentages of H3PW12O40 (heteropolyacid) over a SiO2 support. The bifunctionality of the H3PW12O40/SiO2 catalyst is ascribed to the mutual coexistence of Lewis and Brvinsted acid sites. The Lewis acid sites imparted by active W metal sites adsorb hydrogen proton for catalytic transfer hydrogenation of FUR to FAL, while the predominant Brvinsted acid sites catalyze the hydrolysis of FAL to LA. Consequently, H3PW12O40/SiO2 revealed to be a potential catalyst producing an similar to 51% LA yield under optimized reaction conditions. Moreover, the catalyst was found to be reusable for three catalytic cycles. This study paves the way to develop future biorefinery, particularly direct conversion of FUR to LA over a bifunctional catalyst with a liquid H-donor, in an environmentally benign manner and comply with the green chemistry principles.